Study on nutrient analysis of available varieties of mango kernel of Karnataka - Meti, Renuka; Inamda, Azma (Journal of Postharvest Technology, 2022)
In the present study, the two most consumed mango varieties of Karnataka state, Alphonso and Totapuri, were subjected to analysis of selective nutrient contents in their kernels. The nutrients selected for analysis in this study are ash, moisture, total lipids, protein, carbohydrates, iron, calcium, zinc, vitamin A, vitamin E, and vitamin B12. The amount of nutrients present in these two varieties of mango kernel are as follows: the ash content was 2.00 g/100g and 1.0 g/100g, the moisture content was 5.97%/100g and 7.05%/100g, the total lipids content was 9.74g/100g and 11.45g/100g, the protein content was 7.58g/100g and 7.53g/100g, the carbohydrate content was 74.71g/100g and 69.77g/100g, the iron content was 11.39mg/kg and 12.40mg/kg, the calcium content was 54.71mg/ kg and 170.00mg/kg, the zinc content was 12.27mg/kg and 5.60mg/kg, the vitamin A content was 0.00654mg/100g and 0.00522mg/100g, the vitamin E content was 1.91mg/100g and 1.59mg/100g, and the vitamin B12 content was 0.14mg/100g and 0.12mg/100g of Alphonso and Totapuri mango kernels, respectively.